PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, LEVERAGE, FINANCIAL DISTRESS DAN RISIKO LITIGASI TERHADAP KONSERVATISME AKUNTANSI - Prisila Damayanty; Rofina Masrin (Jurnal Manajemen dan Bisnis, 2022)
This study aims to examine and analyze the influence of managerial ownership structure, leverage, financial distress and litigation risk on accounting conservatism. A sample of 8 companies was obtained from 35 companies using purposive sampling of manufacturing companies in the transportation sub-sector listed on the IDX in the 2017-2020 period. The results of the study found 1) managerial ownership structure has a negative and not significant effect on accounting conservatism, 2) leverage has a negative and significant effect on accounting conservatism, 3) financial distress has a positive and insignificant effect on accounting conservatism, 4) litigation risk has a positive and significant effect on accounting conservatism, 5) while simultaneously managerial ownership structure, leverage, financial distress and litigation risk have a positive and significant effect on accounting conservatism.